Synthesis and redox properties of LixNi2(MoO4)3: a new 3-V class positive electrode material for rechargeable lithium batteries - Prabaharan, S.R.S.; Michael, M.S.; Ramesh, S.; Begam, K.M. (2004)
A new framework type Li(x)Ni(2)(MoO(4))(3) [0 less than or equal to x less than or equal to 4] polyanion compound was synthesized via a glycine-nitrate soft-combustion process at low temperature. The annealed powders were characterized by XRD to confirm the phase formation of the stoichiometric product, Ni(2)(MoO(4))(3) in its non-lithiated state. The morphology of the annealed product was found to be composed of soft agglomerates embedded by ultrafine spherical grains. Electrochemical redox properties of the synthesized product were confirmed by employing the new material as a cathode in lithium-containing test cells in an aprotic electrolyte environment (1 M LiPF(6) in EC + DMC). Slow scan cyclic voltammetry (SSCV) confirmed the redox behavior corresponding to the reduction/oxidation of the transition metals, Ni and Mo between the potential window of 3.5-1.5 V. The lithium insertion/extraction process was confirmed by galvanostatic measurements on the test cells and they exhibited well discernible discharge/charge profiles with a reversible capacity of 170 mAh/g over the potential window of 3.5-1.5 V after the first charge/discharge cycle. Nevertheless, the discharge capacity was found to deteriorate slowly upon repeated cycling, which might presumably be due to disproportion reaction of the host structure beyond the extent of insertion of two lithium ions. (C) 2004 Elsevier B.V. All rights reserved.